HIV and Syphilis Prevalence Among Men Who Have Sex With Men: A Cross-Sectional Survey of 61 Cities in China - Wu, Zunyou (Oxford University Press, 2013)
Background. Human immunodeficiency virus (HIV) has rapidly spread among men who have sex with men (MSM) in China in recent years; the magnitude of the epidemic is unclear. We sought to test 3 hypotheses: (1) The prevalence of both HIV and syphilis among MSM in China is high, (2) the 2 epidemics each have unique geographical distributions, and (3) demographic and sexual behavior characteristics are different among segments of the MSM population in China. Methods. A total of 47 231 MSM from 61 cities in China participated in a cross-sectional survey conducted from February 2008 to September 2009. Demographic and behavioral data were collected and analyzed and blood samples tested for HIV and syphilis. Three subgroups among the broader MSM sample were described. Main outcome measures were HIV and syphilis prevalence. Results. An overall prevalence of 4.9% (2314/47 231; 95% confidence interval [CI], 4.7%–5.1%) for HIV and 11.8% (5552/47 231; 95% CI, 11.5%–12.0%) for syphilis was found. Syphilis-positive MSM had the highest HIV prevalence, 12.5% (693/5552; 95% CI, 11.6%–13.4%). However, correlations between HIV and syphilis prevalence were found in only 3 of 6 geographical regions (Northwest: r = 0.82, P = .0253; East: r = 0.78, P = .0004; and South-central: r = 0.63, P = .0276). Three subgroups—nonlocal MSM, Internet-using MSM, and female-partnering MSM—were found to have different profiles of characteristics and behaviors. Conclusions. HIV and syphilis prevalences among MSM in China are high and the 2 epidemics are largely separate geographically. Three segments of the Chinese MSM population each have different demographic and sexual risk “profiles” that suggest high potential for bridging infection across geographies, generations, and sexes.